Rempah Lombok: Pendekatan Kearifan Lokal sebagai Strategi Penguatan Praktik MPASI bagi Kader Posyandu - Nani Nurhaeni; La Ode Abd Rahman; Astuti Astuti*; Syamikar Baridwan Syamsir; Ayuni Rizka Utami (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Stunting is a problem of chronic malnutrition in young children. Some of the causes of stunting were inappropriate of complementary feeding practices and lack of support from health cadres. One of the stunting locus areas in Indonesia is East Lombok Regency. An education programme needs to be conducted for stunting prevention, such as education of complementary feeding practices and socialisation of the book called "Rempah Lombok". The book was prepared as a guideline for cadres and mothers to provide recommended complementary feeding with local Lombok recipes. The indicator of the success of this activity was done by giving a question-and-answer quiz directly before and after the education process related to complementary feeding practices. The existence of programmes was expected to guide the cadres and mothers more easily and confidently in providing appropriate complementary feeding practices and improving the nutritional status of under-five children in East Lombok.